2004
DOI: 10.1159/000079802
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Lunar Periodicity in Human Spontaneous Abortions

Abstract: The effect of the moon on human reproduction has been scarcely investigated and with controversial results. The present analysis describes a significant effect of extreme perigeal lunar positions on the number of hospitalized spontaneous abortions (n = 1,329) recorded at two university clinics and a public hospital at Padova, Italy, during the years 2000–2003. Spectral analysis evidenced a 205-day period which appears to be correlated with the 206-day periodicity in extreme lunar distances. Circa-septan and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These and an about 10.5-year component similar to the solar activity cycle had been reported earlier (Halberg et al, 2004). Of interest is the about 200day variation detected with the GOSA software (Czaplicki et al 2006), very close to the 205-day change in spontaneous abortions in Padua reported by Valandro et al (2004), which the authors associate with the extreme lunar perigeal positions, a periodicity of the moon in reaching its greatest distance from the earth, later extended to spontaneous abortions in Nové Zámky (Matuška and Mikulecky, 2006). The aim of this work was to provide biologists and biochemists with an easy-to-use, reliable program capable of finding global minima of an arbitrary function.…”
Section: Methodssupporting
confidence: 53%
“…These and an about 10.5-year component similar to the solar activity cycle had been reported earlier (Halberg et al, 2004). Of interest is the about 200day variation detected with the GOSA software (Czaplicki et al 2006), very close to the 205-day change in spontaneous abortions in Padua reported by Valandro et al (2004), which the authors associate with the extreme lunar perigeal positions, a periodicity of the moon in reaching its greatest distance from the earth, later extended to spontaneous abortions in Nové Zámky (Matuška and Mikulecky, 2006). The aim of this work was to provide biologists and biochemists with an easy-to-use, reliable program capable of finding global minima of an arbitrary function.…”
Section: Methodssupporting
confidence: 53%
“…The variation in birth rate has been related to the photoperiod or temperature (affecting hormonal concentrations, sperm quality, or sexual activity) and may also be influenced by sociodemographic factors ( Bobak and Gjonca 2001 ). The variation in spontaneous abortions can be influenced by lunar periodicity ( Valandro et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lunar cycle has been proved to have an impact on human reproduction, in particular fertility, menstruation and birth rate. Even hospitalized spontaneous abortions are significantly associated with the lunar cycle [6]. Given that the most common cause of spontaneous abortion is chromosomal abnormalities of the embryo, we presume that the lunar cycle could influence the occurrence of chromosomal diseases.…”
Section: Introductionmentioning
confidence: 98%